The Enemy of My Enemy Is My Friend: The Warming of Relations between the Moscow Patriarchate and the Vatican during the Pontificate of Benedict XVI - Du Quenoy, Irina (The journal of Eastern Christian studies, 2023)
The year 2016 saw the historic meeting between Pope Francis I and Patriarch Kirill I of the Russian Orthodox Church. Taking place on what was understood as the “neutral” territory of communist Cuba, the meeting sent shockwaves through the Orthodox world as it indicated a warming of relations that, for some, augured the healing of a millennium-long schism and, for others, the capitulation of the Orthodox Church to papal hegemony. Though certainly startling (the meeting was prepared in secret), the summit in Havana could not have occurred without a preparatory process of rapprochement between the two sides. This paper examines this rapprochement as it occurred under the pontificate of Benedict XVI (2005–2013), arguing that it was this process that made Havana possible. While relations between the RCC and ROC post 2016 are outside the scope of this paper, I note that the context of that event suggested that the road forward would remain far from clear as the obstacles to full reconciliation obvious in the preceding period remained salient.